2016
DOI: 10.1371/journal.pone.0149609
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Attitudes towards Medical Research in the United Arab Emirates: Results from the Abu Dhabi Cohort Study (ADCS) Focus Group Discussions

Abstract: BackgroundIn developing medical research, particularly in regions where medical research is largely unfamiliar, it is important to understand public perceptions and attitudes towards medical research. In preparation for starting the first cohort study in the United Arab Emirates, the Abu Dhabi Cohort Study (ADCS), we sought to understand how we could improve the quality of the research process for participants and increase public trust and awareness of research.MethodsWe conducted six focus groups (FG), consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 12 publications
(18 reference statements)
2
21
0
Order By: Relevance
“…This decrease coincided with the reform of its residency training program, leading to the researcher’s conclusion that “it is quite likely that our residents are providing better patient care”. In Abu Dhabi, a study into perceptions and attitudes towards medical research amongst focus group participants noted that the UAE has one of the best healthcare systems in the region [ 47 ]. The UAE has also witnessed a significant growth in Joint Commission International (JCI) accreditation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…This decrease coincided with the reform of its residency training program, leading to the researcher’s conclusion that “it is quite likely that our residents are providing better patient care”. In Abu Dhabi, a study into perceptions and attitudes towards medical research amongst focus group participants noted that the UAE has one of the best healthcare systems in the region [ 47 ]. The UAE has also witnessed a significant growth in Joint Commission International (JCI) accreditation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first stage of the pilot study (September to December 2014) was a series of focus group discussions with potential participants to develop and optimize the participants’ information material and study protocols, the results of which has been published elsewhere [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another very important barrier in research activities is the approval by the institutional ethical committee. Most of the time ethical committee documentation is very exhaustive, and a lot of objections distract the young researchers [ 29 ]. But our survey revealed that with the advance in seniority of the students, when the young researchers get to understand the procedure better, this barrier occurs less, i.e.…”
Section: Main Textmentioning
confidence: 99%